Seed germination ecology of meadow knapweed (Centaurea × moncktonii) populations in New York State, USA. Issue 1 (3rd January 2021) - DiTommaso, Antonio; Milbrath, Lindsey R.; Marschner, Caroline A.; Morris, Scott H.; Westbrook, Anna S.
Abstract: The introduced meadow knapweed ( Centaurea × moncktonii C.E. Britton), a hybrid of black ( Centaurea nigra L.) and brown ( Centaurea jacea L.) knapweeds, is increasingly common in pastures, meadows, and waste areas across many U.S. states, including New York. We evaluated the effects of temperature, light, seed stratification, scarification, and population on percent germination in four experiments over 2 yr. Percent germination ranged from 3% to 100% across treatment combinations. Higher temperatures (30:20, 25:15, and sometimes 20:10 C day:night regimes compared with 15:5 C) promoted germination, especially when combined with the stimulatory effect of light (14:10 h L:D compared with continuous darkness). Under the three lowest temperature treatments, light increased percent germination by 15% to 86%. Cold-wet seed stratification also increased germination rates, especially at lower germination temperatures, but was not a prerequisite for germination. Scarification did not increase percent germination. Differences between C. × moncktonii populations were generally less significant than differences between temperature, light, and stratification treatments. Taken together, these results indicate that C. × moncktonii is capable of germinating under a broad range of environments, which may have facilitated this species' range expansion in recent decades. However, C. × moncktonii also shows evidence of germination polymorphism: some seeds will germinate under suboptimal conditions, while others may remain dormant until the abiotic environment improves. Subtle differences in dormancy mechanisms and their relative frequencies may affect phenological traits like the timing of seedling emergence and ultimately shape the sizes and ranges of C. × moncktonii populations.